The Effectiveness of PowerPoint-Assisted Redox Learning: A Quasi-Experimental Study with Independent Pretest–Posttest Samples in Grade XII Students - Mukti Inayati; Fitria Fatichatul Hidayah (Universitas Lampung, 2026)
Abstract: The Effectiveness of PowerPoint-Assisted Redox Learning: A Quasi-Experimental Study with Independent Pretest–Posttest Samples in Grade XII Students. Objectives: This study examined the effectiveness of PowerPoint (PPT)-assisted instruction on Grade XII students’ learning outcomes in redox reactions by comparing achievements between pretest and posttest respondent groups. Methods: A quantitative quasi-experimental approach with an independent pretest–posttest design was employed. Participants were Grade XII students (population 36) with 33 respondents completing the pretest and 24 respondents completing the posttest. The instrument was a Google Form-based redox concept test (0–100). Data were analyzed using the Mann–Whitney U test (α = 0.05) and effect size was calculated using r=∣Z∣/​.Findings: The posttest group showed a higher mean rank (35.69) than the pretest group (24.14). The Mann–Whitney test indicated a significant difference between groups (U = 235.500; Z = −3.152; p = 0.002, two-tailed). The effect size was r ≈ 0.42, indicating a medium-to-large effect.Conclusion: PPT-assisted redox learning was associated with significantly better posttest performance and a practically meaningful effect. However, because pretest and posttest respondents were not identical, results should be interpreted as a comparison of two independent respondent groups before–after instruction.